Association between soil-transmitted helminthiasis and hemoglobin concentration in primary school children - Rita Angraini; Y Dimyati; Bidasari Lubis; Syahril Pasaribu; Chairuddin P Lubis (Paediatrica Indonesiana, 2005)
Objectives To determine the association between intestinal hel-minthiasis and hemoglobin (Hb) concentration and to observe theeffect of single dose albendazole treatment on Hb concentration.Methods An experimental study was carried out from March toJuly 2002 on primary school children at Suka Village, Tiga PanahSubdistrict, Karo Regency, North Sumatera Province. From 366children who suffered from helminthiasis, 113 were selected assubjects by simple random sampling. Subjects were treated with asingle oral dose of 400 mg albendazole. Hb concentration wasexamined using the cyanide method twice i.e., prior to and threemonths after treatment with albendazole.Results It was found that among 113 subjects, the prevalences ofAscaris lumbricoides, Trichuris trichiura, and mixed infestation were18.3%, 40.4%, and 41.3%, respectively, while the prevalence ofanemia was 33.0%. There was no significant difference in age,gender, nutritional status, and mean Hb concentration betweenchildren suffering from the different types of worm infestation(P>0.05). For each type of infestation, there were significant differ-ences in mean Hb concentration and anemia prevalence beforeand after treatment (P<0.05).Conclusions There was no difference between the Hb concen-trations of children suffering from Ascaris lumbricoides, Trichuristrichiura, and mixed-type worm infestations. Single dose 400 mgalbendazole was beneficial in increasing Hb concentration andreducing the occurrence of anemia